Optimizing English learning through outcome-based education and Moodle integration in higher education - Sriyanto, Agus; Prasetya, Rizky Eka; Hidayat, Ravindra Safitra (Journal of English Language Teaching Innovations and Materials (Jeltim), 2024)
This study investigates the impact of Moodle-supported Outcome-Based Learning (OBL) on the acquisition of English language competencies among higher education students. The purpose was to explore how varying levels of interaction with Moodle influence student performance in Reading, Writing, and Speaking. Utilizing a mixed-methods research design, the study combined quantitative analysis of student scores with qualitative insights from participant feedback. The findings reveal that students who engaged more frequently with Moodle demonstrated higher and more consistent performance across all language competencies compared to those with lower engagement or no interaction with Moodle. The study also found that the development of these competencies is largely independent, as indicated by weak correlations between Reading, Writing, and Speaking scores. These results underscore the importance of tailored instructional strategies within Moodle to effectively target each specific language skill. The study concludes that while Moodle is a powerful tool for enhancing language learning, its effectiveness is maximized when activities are designed to address the distinct needs of each competency. The findings have significant implications for educators and curriculum designers, highlighting the need for a differentiated approach to using Moodle in language education.